Learning approach and its relationship to type of media use and frequency of media-multitasking. (July 2019) - Law, Anna S; Stock, Rosemary
Research has demonstrated that learning is impaired if students multitask with media while encountering new information. However, some have gone further and suggested that media-multitasking (as a general activity) may have a negative impact on cognitive control processes. If this were the case, students who are heavy media-multitaskers generally would have difficulties with goal-directed behaviour and organising their time effectively to meet their learning goals. The study described here explored links between total levels of self-reported media-multitasking, academic achievement and approaches to learning. Well-established measures of media-multitasking and learning approach were given to 307 students. Total levels of media-multitasking did not relate to either learning approach or academic achievement. However, surface learning approach related negatively to academic achievement and time spent engaging with printed media. Deep learning approach was positively related to time spent using printed media, email and other computer applications. These findings suggest that patterns of media use differ according to current learning approach, and that these patterns may be more relevant for learning than overall tendency to media-multitask.